2020
DOI: 10.1155/2020/7516789
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Gravity Correction to Hawking Radiation of the 2+1-Dimensional Wormhole

Abstract: We carry out the Hawking temperature of a 2+1-dimensional circularly symmetric traversable wormhole in the framework of the generalized uncertainty principle (GUP). Firstly, we introduce the modified Klein-Gordon equation of the spin-0 particle, the modified Dirac equation of the spin-1/2 particle, and the modified vector boson equation of the spin-1 particle in the wormhole background, respectively. Given these equations under the Hamilton-Jacobi approach, we analyze the GUP effect on the tunneling probabilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 114 publications
0
3
0
Order By: Relevance
“…We will be referencing [16] and [17], i.e. for [16] we have a rate of production from the wormhole mouth we can quantify as ( )…”
Section: The Big Picture Polarization Of Signals From a Wormhole Mouth May Affect Gw Astronomy Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We will be referencing [16] and [17], i.e. for [16] we have a rate of production from the wormhole mouth we can quantify as ( )…”
Section: The Big Picture Polarization Of Signals From a Wormhole Mouth May Affect Gw Astronomy Investigationsmentioning
confidence: 99%
“…Whereas we have from [17] a probability for "scalar" particle production from the wormhole given by ( )…”
Section: The Big Picture Polarization Of Signals From a Wormhole Mouth May Affect Gw Astronomy Investigationsmentioning
confidence: 99%
“…Black holes are laboratories where quantum gravitational effects cannot be neglected and GUP applications can be tested. In the context of this thought, it is reported that the thermodynamic parameters of a black hole depend not only on the black hole properties but also on the properties of the tunnelled particles [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. In light of these discussions, we focus on the thermodynamic quantities of the charged dRGT black hole by taking into account the quantum gravity effects.…”
Section: Introductionmentioning
confidence: 99%